Resolution of Religion Conflicts Through Communication Strategies in Gharib Fil Ma'na Hadiths - Azzuhri, Muhandis; Farmawati, Cintami; Amalia, Zahida Putri (JURNAL PENELITIAN, 2018)
Religious conflicts are often caused by misunderstandings arising due to mismatch in the ways of communication. Effective communication along with a sincere desire to resolve conflicts will be more likely to make resolution of religious conflicts successful. The focus of this study is to describe religious conflict resolution through the communication strategy of the Prophet Muhammad in the hadiths "Fil Gharib Ma'na" in Kutubus Sittah which are the books of Shahih Bukhari, Sahih Muslim, Turmudzi, Nasai, Abu Dawood and Ibn Majah. Gharib fil ma'na is hadiths which contain non-Arabic loan words. This research is a library research. The data were obtained from various literatures. The method of data collection uses documentation techniques, which are divided into primary data and secondary data. The results of the study of the gharib fil ma’na hadiths with speech action theory and resolution of religious conflict through communication strategies in the speech acts of the Prophet Muhammad were carried out in various ways namely two-way communication, body language, verbal communication and intonation, audio visual communication and correspondence.